Formulation and Evaluation Studies of Floating Matrix Tablets of Nifedipine - S.K. SREEKANTH; S. PALANICHAMY; T. RAJA SEKHARAN; A. THANGA THIRUPATHI (International Journal of Pharma and Bio Sciences, 2010)
The main aim of the study was to design and evaluate nifedipine floating matrix tablets. Hydroxyprophyl methyl cellulose (HPMC K100M) was used as a polymer. About 15-35 % of HPMC can be used as a polymer in the extended release formulations. So, here the polymer was used in the range of 16-36 %. Sodium bicarbonate (40%) is used as a gas generating agent. It can be used in the range of 25-50 %. The granules are prepared by wet granulation method. The prepared granules were evaluated for the bulk density, tapped density, bulkiness, angle of repose, compressibility index and hausner ratio. The values indicate good flow property. The compressed tablets were evaluated for hardness, uniformity of weight, friability, drug content, buoyancy lag time and duration of buoyancy. All the readings are within the prescribed limits. There was no interaction between the drug, polymer and excipients it was found out by IR studies. The in vitro release data were fitted to different order of reactions such as zero order, first order, higuchis reaction, Hixson crowell reaction and korsmeyer peppas reaction. The drug release follows Korsmeyers – Peppas reaction. The mechanism of drug release is by non-fickian motion. The in vitro drug release data indicate that the release of the drug depends upon the proportion of polymer present in the formulation. As the polymer ratio increases the release rate of the drug is prolonged.